Інтродукція представників родини Berberidaceae Juss. в умовах ботанічного саду НУБіП України - Iakobchuk, O.M.; Kolesnichenko, O.V.; Hrigoryuk, I.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The data on the introduction of representatives of the genera Berberis L. and Mahonia Nutt. (Berberidaceae Juss.) in the collection of Botanical Garden of National University of Life and Environmental Sciences of Ukraine (Kyiv) are presented. An analysis extent of winter resistance, reproductive capacity and ways of breeding species of plants in the family Berberidaceae is made.